Electric motors and drives : fundamentals, types, and applications - Hughes, Austin; Drury, Bill (Amsterdam : Newnes, 2013)
Electric Motors and Drives is intended for non-specialist users of electric motors and drives, filling the gap between maths- and theory-based academic textbooks and the more prosaic 'handbooks', which provide useful detail but little opportunity for the development of real insight and understanding. The book explores all of the widely-used modern types of motor and drive, including conventional and brushless D.C., induction motors and servo drives, providing readers with the knowledge to select the right technology for a given job. The third edition includes additional diagrams and worked examples throughout. New topics include digital interfacing and control of drives, direct torque control of induction motors and current-fed operation in DC drives. The material on brushless servomotors has also been expanded. Austin Hughes' approach, using a minimum of maths, has established Electric Motors and Drives as a leading guide for electrical engineers and mechanical engineers, and the key to a complex subject for a wider readership, including technicians, managers and students. Acquire knowledge of and understanding of the capabilities and limitations of motors and drives without struggling through unnecessary maths and theory Updated material on the latest and most widely-used modern motors and drives, including brushless servomotors New edition includes additional diagrams and worked examples throughout.
Electric motors - the basics-- introduction to power electronic converters for motor drives-- conventional D.C. motors-- D.C. motor drives-- induction motors - rotating field, slip and tongue-- induction motors - operation from 50/60 Hz supply-- variable frequency operation of induction motors-- inverter-fed induction motor drives-- synchronous and brushless permanent magnet machines and drives-- stepping and switched-reluctance motors-- motor-drive selection
Includes index.
Keywords: ELECTRIC MOTORS